Using 3D Animations in Teaching Chemistry - Fiscarelli, Silvio Henrique [UNESP]; Bizelli, Maria Helena Sebastiana Sahão [UNESP]; Fiscarelli, Patricia Eliane (My University, 2011)
This paper discuss possibilities of use of 3D animation as a tool for teaching Chemistry support. The research proposes to investigate the conception process and development of educational animations to use in a Blended Learning environment in undergraduate chemistry. Associated with general chemistry teachers, were raised the demands and difficulties on the content transmission, and the most relevant topics, about "Atomic Theory" with propose to create appropriate animations to meeting needs of themes. Thinking about offering more dynamic materials, we elaborate animations in a format of "micro-documentary", with a length between 4 and 7 minutes. We use the narration aloud to the subject-matter understanding, leaving the external text as a complement of the animation. The conclusions are positives, students accepted well the format and they proved are able to remember, organize and systematize several information presented in animations. These skills don't ensure knowledge acquisition, but may be considered prerequisites to learning occur.